Penerapan Virtual Privat Network (VPN) untuk Keamanan Data - Fasrian Mauren Niella Hura; Agus Damai Lase; Devi Chrisman Lase (LKP KARYA PRIMA KURSUS, 2026)
This study addresses the increasingly crucial issues of data security and digital privacy amidst the rise in online activity. Using library research, the study examined various scientific literature, journals, cybersecurity agency reports, and other academic sources to understand two key issues: user vulnerability when connecting to public networks and the low level of public literacy regarding data protection mechanisms. The study's findings indicate that public networks remain one of the most vulnerable points in digital communication due to weak encryption and the high risk of data interception. Furthermore, the public's lack of understanding of privacy protection technology exacerbates the situation, as users often neglect security measures for the sake of convenience. The literature analysis demonstrates that data protection is not solely dependent on technology but is also largely determined by users' awareness and understanding. Therefore, this study concludes that digital security solutions must balance technological and educational aspects. This approach will help users better understand the risks they face and utilize protection technology more effectively to safeguard their digital privacy.